2014
DOI: 10.1099/mic.0.081968-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytosine chemoreceptor McpC in Pseudomonas putida F1 also detects nicotinic acid

Abstract: Soil bacteria are generally capable of growth on a wide range of organic chemicals, and pseudomonads are particularly adept at utilizing aromatic compounds. Pseudomonads are motile bacteria that are capable of sensing a wide range of chemicals, using both energy taxis and chemotaxis. Whilst the identification of specific chemicals detected by the ¢26 chemoreceptors encoded in Pseudomonas genomes is ongoing, the functions of only a limited number of Pseudomonas chemoreceptors have been revealed to date. We repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…McpC (orthologous to PP0584) ( Fig. 3) was identified as a chemoreceptor for cytosine (172) and nicotinic acid (173). Another study led to the identification of a chemoreceptor, termed PcaY, which is an ortholog of PP2643 (Fig.…”
Section: Pseudomonasmentioning
confidence: 99%
“…McpC (orthologous to PP0584) ( Fig. 3) was identified as a chemoreceptor for cytosine (172) and nicotinic acid (173). Another study led to the identification of a chemoreceptor, termed PcaY, which is an ortholog of PP2643 (Fig.…”
Section: Pseudomonasmentioning
confidence: 99%
“…To identify the chemoreceptor for alcohols, mutant strains with various receptor gene deletions were screened for the ability to respond to ethanol. We have been working toward generating a "gutted" strain lacking all 27 of the putative MCP and MCP-like genes in P. putida 31), the aromatic acid receptor PcaY (16), and the nicotinic acid/cytosine receptor McpC (13,18). In addition, four genes encoding receptors of unknown function were also deleted in this strain (locus tags Pput_0342, Pput_3459, Pput_4234, and Pput_4764).…”
Section: Resultsmentioning
confidence: 99%
“…A conserved set of cytoplasmic chemotaxis proteins (CheA, CheY, CheW, CheR, and CheB), together with Ն20 membrane-spanning methylaccepting chemotaxis proteins (MCPs), mediate responses to a wide range of organic and inorganic attractants in pseudomonads (9,10). For example, known attractants for Pseudomonas putida strains include various amino acids, organic acids (11,12), purines and pyrimidines (13,14), polyamines (15), aromatic acids (16)(17)(18), and aromatic hydrocarbons (19)(20)(21). However, to our knowledge, chemotaxis to alcohols by Pseudomonas spp.…”
mentioning
confidence: 96%
“…It was determined that cytidine was degraded by the enzymes nucleoside hydrolase, uridine phosphorylase and cytosine deaminase [118]. Another study found that the pyrimidine base cytosine served as a chemoattractant for P. putida, with cytosine deaminase degrading cytosine to uracil, which provides a nitrogen source to the cells [130,131].…”
Section: Pseudomonas Putida Homology Groupmentioning
confidence: 99%